HOLOCENE VEGETATION VARIATIONS AND THE ASSOCIATED ENVIRONMENTAL CHANGES IN THE WESTERN PART OF THE CHINESE LOESS PLATEAU - Feng Z.-D.; Ma Y.Z.; Tang L.Y.; Wang H.B.; Liu K.-b. (My University, 2006)
The western part of the Chinese Loess Plateau has experienced a series of environmental changes during the Holocene. A desert-steppe of late glacial was succeeded by a forest-steppe from 8850 to 7540 14C years BP, and a Pinus-dominated forest occupied the landscape from 7540 to 6560 14C years BP. A deciduous forest of high density and diversity existed from 6560 to 5790 14C years BP. Afterwards the vegetation changed to a Pinus-dominated forest-steppe (5790-4950 14C years BP) and then to an Ulmus-dominated forest-steppe (4950 to ~ 4000 14C years BP). The vegetation subsequently changed to a steppe from ~ 4000 to 3120 14C years BP and further to a desert-steppe from 3120 to 2900 14C years BP. After a period of vegetation improvement (steppe) from 2900 to 2460 14C years BP, a desert-steppe resumed (2460-2020 14C years BP). Steppe vegetation was re-established around 2020 14C years BP and seems to have then deteriorated again around 1000 14C years BP. The general trend of aforementioned climatic changes is proposed here to have been modulated by the insolation changes. Specifically, the insolation started to increase around 15,000 years BP and peaked around 9000 years BP when the obliquity-driven seasonality reached a maximum with the summer insolation being about 8% more than the present. As a result, tropical Holocene SST increased steadily from ~ 10,000 to ~ 6,000 years BP, thus effectively strengthening the East Asian summer monsoon. In addition, the documented high temperatures from 10,000 to 4000 years BP in high northern latitudes might have weakened the strength of the winter monsoon and thus enhanced the strength of the summer monsoon probably via lengthening of the rainy season, directly contributing to the "megahumid" climate between 10,000 and 4000 years BP in the western part of the Chinese Loess Plateau. © 2006 Elsevier B.V. All rights reserved.
Keywords: CHINESE LOESS PLATEAU; HOLOCENE CLIMATE; VEGETATION HISTORY; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен